2019
DOI: 10.1111/1462-2920.14653
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling spatiotemporal variability of arbuscular mycorrhizal fungi in a temperate grassland plot

Abstract: Summary Soils provide a heterogeneous environment varying in space and time; consequently, the biodiversity of soil microorganisms also differs spatially and temporally. For soil microbes tightly associated with plant roots, such as arbuscular mycorrhizal fungi (AMF), the diversity of plant partners and seasonal variability in trophic exchanges between the symbionts introduce additional heterogeneity. To clarify the impact of such heterogeneity, we investigated spatiotemporal variation in AMF diversity on a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 98 publications
1
20
0
Order By: Relevance
“…In addition, a rather small proportion ( ca . 20%) of explained variation in arbuscular mycorrhizal fungi communities was observed within temperate grassland soils at a small scale (Goldmann et al, ). Future studies ought to take into more environmental variables, such as soil temperature and trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a rather small proportion ( ca . 20%) of explained variation in arbuscular mycorrhizal fungi communities was observed within temperate grassland soils at a small scale (Goldmann et al, ). Future studies ought to take into more environmental variables, such as soil temperature and trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses showed that this grassland plot features considerable spatio-temporal variability in plant productivity and diversity (Klaus et al, 2016), complex dependencies between general habitat properties and microbial parameters such as phospholipid fatty acid (PLFA) profiles and enzymatic activities (Regan et al, 2014(Regan et al, , 2017, as well as between ammonia-and nitrite-oxidizing microorganisms (Stempfhuber et al, 2015). High turnover of arbuscular mycorrhizal fungi, likely driven by stochastic processes (Goldmann et al, 2019), and taxon-dependent influences of edaphic variables on protists (Fiore-Donno et al, 2019) were previously described as well.…”
Section: Sample Acquisitionmentioning
confidence: 99%
“…Moreover, it was previously shown that both the plant species identity and intraspecific plant diversity can affect the associated microbiomes [3][4][5]. Besides seasonal differences in microbial diversity and activity in soils [6][7][8], the plant-development stage led to variability in associated microbiomes [9]. Schematic overview of the experimental design: (a) In October 2011 beech nuts were collected from four forest plots within the three sites of the Biodiversity Exploratories, i.e., Schwäbische Alb, Hainich-Dün, and Schorfheide-Chorin; (b) beech seedling grew in a greenhouse at Göttingen University; (c) in October 2012 beech seedling of different progenies were out-planted to nine forest plots per site; (d) in September 2014 and November 2017 beech trees on five Schorfheide-Chorin plots were sampled; (e) we collected roots and the attached rhizosphere soil and gained a total of 60 samples (three progenies × five plots × two sampling years × two compartments) for subsequent analyses of the beech rootassociated fungal mycobiome.…”
Section: Introductionmentioning
confidence: 99%